Raising children in America: Korean parents' experiences. Issue 6 (1st February 2012) - CHOI, H.; DANCY, B. L.; LEE, J.
<x xml:space="preserve">Abstract</x> Accessible summary Regardless of the known risks for conflicted parent–child relationships and mental health problems among Korean American families, our knowledge of their perceptions of parenting stress and parent–child relationships is very limited, particularly knowledge obtained from parents' perspectives. The main stresses that parents encountered while raising their adolescent children in the USA were inability to advocate for children, feeling uneasy and insecure about incompatible American culture, ambivalence towards children's ethnic identities, and feeling alienated. As parents encountered those challenges and difficulties, they became doubtful of their decisions to move to the USA and felt inadequate, ashamed, guilty, regretful and powerless. The present study highlights the need for and importance of providing intervention programmes for parents, particularly programmes that would empower parents and strengthen parent–child relationships. Abstract This qualitative description study was designed to describe Korean American parents' perceptions of challenges and difficulties they encounter while raising their children in the USA. A convenience sampling of 21 parents of adolescents aged 11–14 years recruited from the Midwest Korean American community participated in the study. Data were collected using in‐depth, face‐to‐face interviews, which took place in agreed‐upon, convenient locations. All interviews were audiotaped and transcribed in Korean and the transcripts were translated into English. Qualitative content analysis revealed that the main stresses that parents encountered while raising their children in the USA were inability to advocate for children, feeling uneasy and insecure about incompatible American culture, ambivalence towards children's ethnic identities, and feeling alienated. In relation to these stresses, parents often felt inadequate, ashamed, guilty, regretful and powerless. The findings demonstrated the importance of understanding parents' feelings that are deeply embedded in the conflicted parent–child relationships and their perceptions of being parents in the USA. The present study highlights the need for and importance of providing intervention programmes for parents, particularly programmes that would empower parents, strengthen parent–child relationships and address ways to integrate two very different cultures while upholding ethnic identity and pride.